The price of NFL fandom: An exploratory study of the past, present, and future purchasing power of NFL fans - Fountain, J. J.; Finley, P. S. (The Sport Journal, 2010)
Concerns regarding gentrification of sports and the loss of middle-income fans have increased throughout the years, as ticket prices have continued to increase well beyond the rate of inflation for professional sports. This research focused on the changes in purchasing power for fans wishing to attend live games in the National Football League from 1991 to 2009 and then made subsequent forecasts for purchasing power 10 years into the future, should current pricing trends continue unabated. The Fan Cost Index (FCI) was utilized to compare purchasing power over time. Results showed that average FCI price for the league increased by 75% beyond inflation from 1991 to 2009. Purchasing power for fans from all the teams in the study diminished in some fashion from 1991 to 2009. However, eight of the 24 teams in the study severely reduced fan purchasing power, including a 50% or more reduction in the number of tickets alone. If pricing trends continue, the league could experience decreased attendance, particularly from fans in the lower income brackets.